Transcriptomic and epigenetic regulation of disuse atrophy and the return to activity in skeletal muscle. Issue 12 (17th August 2017) - Fisher, Andrew G.; Seaborne, Robert A.; Hughes, Thomas M.; Gutteridge, Alex; Stewart, Claire; Coulson, Judy M.; Sharples, Adam P.; Jarvis, Jonathan C.
ABSTRACT: Physical inactivity and disuse are major contributors to age‐related muscle loss. Denervation of skeletal muscle has been previously used as a model with which to investigate muscle atrophy following disuse. Although gene regulatory networks that control skeletal muscle atrophy after denervation have been established, the transcriptome in response to the recovery of muscle after disuse and the associated epigenetic mechanisms that may function to modulate gene expression during skeletal muscle atrophy or recovery have yet to be investigated. We report that silencing the tibialis anterior muscle in rats with tetrodotoxin (TTX)—administered to the common peroneal nerve—resulted in reductions in muscle mass of 7, 29, and 51% with corresponding reductions in muscle fiber cross‐sectional area of 18, 42, and 69% after 3, 7, and 14 d of TTX, respectively. Of importance, 7 d of recovery, during which rodents resumed habitual physical activity, restored muscle mass from a reduction of 51% after 14 d TTX to a reduction of only 24% compared with sham control. Returning muscle mass to levels observed at 7 d TTX administration (29% reduction). Transcriptome‐wide analysis demonstrated that 3714 genes were differentially expressed across all conditions at a significance of P ≤ 0.001 after disuse‐induced atrophy. Of interest, after 7 d of recovery, the expression of genes that were most changed during TTX had returned to that of the sham control. The 20 most differentially expressed genes after microarray analysis were identified across all conditions and were cross‐referenced with the most frequently occurring differentially expressed genes between conditions. This gene subset included myogenin (MyoG), Hdac4, Ampd3, Trim63 (MuRF1), and acetylcholine receptor subunit a1 (Chrna1). Transcript expression of these genes and Fboxo32 (MAFbx), because of its previously identified role in disuse atrophy together with Trim63 (MuRF1), were confirmed by real‐time quantitative RT‐PCR, and DNA methylation of their promoter regions was analyzed by PCR and pyrosequencing. MyoG, Trim63 (MuRF1), Fbxo32 (MAFbx), and Chrna1 demonstrated significantly decreased DNA methylation at key time points after disuse‐induced atrophy that corresponded with significantly increased gene expression. Of importance, after TTX cessation and 7 d of recovery, there was a marked increase in the DNA methylation profiles of Trim63 (MuRF1) and Chrna1 back to control levels. This also corresponded with the return of gene expression in the recovery group back to baseline expression observed in sham‐surgery controls. To our knowledge, this is the first study to demonstrate that skeletal muscle atrophy in response to disuse is accompanied by dynamic epigenetic modifications that are associated with alterations in gene expression, and that these epigenetic modifications and gene expression profiles are reversible after skeletal muscle returns to normal activity.—Fisher, A. G., Seaborne, R. A., Hughes, T. M., Gutteridge, A., Stewart, C., Coulson, J. M., Sharples, A. P., Jarvis, J. C. Transcriptomic and epigenetic regulation of disuse atrophy and the return to activity in skeletal muscle. FASEB J. 31, 5268–5282 (2017). www.fasebj.org